Polatuzumab vedotin in combination with immunochemotherapy in patients with previously untreated diffuse large B-cell lymphoma: an open-label, non-randomised, phase 1b–2 study. Issue 7 (July 2019) - Tilly, Hervé; Morschhauser, Franck; Bartlett, Nancy L; Mehta, Amitkumar; Salles, Gilles; Haioun, Corinne; Munoz, Javier; Chen, Andy I; Kolibaba, Kathryn; Lu, Dan; Yan, Mark; Penuel, Elicia; et al.
Summary: Background: Polatuzumab vedotin, an antibody–drug conjugate targeting the CD79b component of the B-cell receptor, has demonstrated activity as a single agent and in combination with rituximab in relapsed or refractory diffuse large B-cell lymphoma. In this study, we evaluated the safety and preliminary activity of polatuzumab vedotin in combination with rituximab or obinutuzumab and cyclophosphamide, doxorubicin, and prednisone (CHP) in patients with previously untreated diffuse large B-cell lymphoma. Methods: This was an open-label, non-randomised study composed of a phase 1b dose escalation and a phase 2 dose expansion at 11 hospitals and health centres in the USA and France. Patients aged 18 years or older with B-cell non-Hodgkin lymphoma were eligible. Exclusion criteria included peripheral neuropathy with grade greater than 1, major surgery within 4 weeks before enrolment, known CNS involvement of lymphoma, and uncontrolled heart disease. Phase 1b dose escalation had a three-plus-three design and established the recommended phase 2 dose. Phase 2 expansion evaluated the recommended phase 2 dose of polatuzumab vedotin in patients with newly diagnosed diffuse large B-cell lymphoma with an International Prognostic Index (IPI) of 2–5. Patients received cyclophosphamide 750 mg/m 2 on day 1 intravenously, doxorubicin 50 mg/m 2 on day 1 intravenously, and prednisone 100 mg once daily on days 1–5 of each 21-day cycle orally (CHP), plus either rituximab 375 mg/m 2 intravenously on day 1 of each cycle (R-CHP) or obinutuzumab 1000 mg intravenously on days 1, 8, and 15 of cycle 1 and on day 1 of the following cycles (G-CHP). Polatuzumab vedotin was administered on day 2 of cycles 1 and 2, and on day 1 of the following cycles at 1·0–2·4 mg/kg during the escalation phase and at the recommended phase 2 dose during the expansion phase. Treatment could last six or eight cycles, depending on investigator preference. The primary endpoints of the study were safety and tolerability, and determination of the maximum tolerated dose (or recommended phase 2 dose) of polatuzumab vedotin. All endpoints were analysed per protocol in the safety evaluable population, defined as all patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT01992653 . Findings: Between Dec 4, 2013, and July 26, 2016, 85 patients were enrolled. 82 patients were included in the safety and activity evaluable populations, 25 in phase 1b and 57 in phase 2. In light of information from other studies using polatuzumab vedotin reported during this study, in which the safety profile associated with exposure to polatuzumab vedotin at doses higher than 1·8 mg/kg every 3 weeks was not outweighed by any clinical benefit, the recommended phase 2 dose was set to 1·8 mg/kg in the R-CHP cohort and no higher doses were explored in this study. 66 patients with newly diagnosed diffuse large B-cell lymphoma received the polatuzumab vedotin recommended phase 2 dose (45 R-CHP; 21 G-CHP). In 66 patients with diffuse large B-cell lymphoma who received the recommended phase 2 dose, the most common adverse events of grade 3 or worse were neutropenia (20 [30%]), febrile neutropenia (12 [18%]), and thrombocytopenia (six [9%]). Among the 70 patients (any histology) who received the recommended phase 2 dose, 19 (27%) had grade 1 peripheral neuropathy, eight (11%) grade 2, and two (3%) grade 3. Four deaths were reported during follow-up: two treatment-related (one complication of atrial fibrillation and one septic shock) and two due to disease progression. As of the cutoff date of Dec 29, 2017, median follow-up time was 21·5 months (IQR 16·7–24·3) for the untreated diffuse large B-cell lymphoma cohort treated at the polatuzumab vedotin recommended phase 2 dose. 59 (89%) patients achieved an overall response at end of treatment (51 [77%] patients had a complete response, and eight [12%] patients had a partial response). Interpretation: The safety of incorporating polatuzumab vedotin to R-CHP or G-CHP was as expected and managable. Preliminary clinical activity in newly diagnosed diffuse large B-cell lymphoma seems promising and encouraged a phase 3 trial comparing polatuzumab vedotin with R-CHP to R-CHOP. Funding: F Hoffmann-La Roche/Genentech.